Impact of On the Job Training Quality for New Employee Competency at AirNav Indonesia JATSC - Angga Fachzona; Lina Rosmayanti; Emilia Rahajeng Larasati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
AirNav Indonesia plays a strategic role in ensuring safe and efficient air traffic operations, particularly at the Jakarta Air Traffic Service Center (JATSC), which operates in a complex and high-risk environment. This study aims to examine the impact of On-the-Job Training (OJT) quality on the competency of new employees at JATSC. OJT quality is assessed through indicators such as curriculum clarity, instructor competence, relevance of training materials, evaluation processes, and feedback mechanisms, while employee competency is measured in terms of technical skills, readiness for independent work, decision-making ability, adaptability to operational pressure, and professionalism. This research adopts a quantitative approach with a descriptive-correlational design. Data were collected from 89 respondents using structured questionnaires, supported by limited observations. The data were analyzed through validity and reliability testing, normality testing, correlation analysis, and simple linear regression. The results show that OJT quality has a positive and significant influence on new employee competency. Higher-quality OJT is associated with improved technical mastery, stronger decision-making capability, and better adaptation to operational demands. The study concludes that effective and well-structured OJT is essential for developing competent personnel who can support aviation safety and operational effectiveness at JATSC